2018
DOI: 10.1186/s40665-018-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a millennium drought on butterfly faunal dynamics

Abstract: Background: Climate change is challenging plants and animals not only with increasing temperatures, but also with shortened intervals between extreme weather events. Relatively little is known about diverse assemblages of organisms responding to extreme weather, and even less is known about landscape and life history properties that might mitigate effects of extreme weather. Our aim was to address this knowledge gap using a multi-decadal dataset of 163 butterfly species that recently experienced a millennium-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 43 publications
7
41
0
Order By: Relevance
“…2) have a negative association through time with minimum temperatures, which is consistent with a previous analysis, focused on species richness (27), that hypothesized rising minimum temperatures as a driver of declining montane butterflies. The association with precipitation sensitivity suggests that a successful subset of the montane fauna not only persists with warming nights but is able to take advantage of the highly variable precipitation of the region (27).…”
Section: On the Geography Of Biotic Response To Climate Changesupporting
confidence: 89%
See 3 more Smart Citations
“…2) have a negative association through time with minimum temperatures, which is consistent with a previous analysis, focused on species richness (27), that hypothesized rising minimum temperatures as a driver of declining montane butterflies. The association with precipitation sensitivity suggests that a successful subset of the montane fauna not only persists with warming nights but is able to take advantage of the highly variable precipitation of the region (27).…”
Section: On the Geography Of Biotic Response To Climate Changesupporting
confidence: 89%
“…The multifaceted nature of climate change is illustrated by the fact that nighttime temperatures are warming faster than daytime conditions (26), and the consequences for insects are poorly-understood but potentially serious, including reduced time for recovery from daytime heat stress, and indirect effects through plants (26). In the mountains of California, rising average daily minimum temperatures had some of the most dramatic negative effects on insects, especially in combination with drier years (27). Rising minimum temperatures in particular seasons might impact insects through effects on critical overwintering stages.…”
Section: On Changing Maximums Minimums Means and Variancementioning
confidence: 99%
See 2 more Smart Citations
“…Declines have been severe in areas highly impacted by human activity, such as industrialized agricultural landscapes, but ongoing insect declines are not restricted to farms or the footprints of suburban sprawl. Fewer butterflies have been observed per year at elevations in the Sierra Nevada Mountains of California high enough to be removed from the most direct effects of development (Forister et al, 2018), and repeated surveys in a protected forest in Costa Rica have found declines in entire genera of tropical moths (Salcido, Forister, Lopez, & Dyer, 2019).…”
Section: Introductionmentioning
confidence: 99%